Two-parameter kinematic theory for punching shear in steel fiber reinforced concrete slabs. (15th February 2020) - Kueres, Dominik; Polak, Maria Anna; Hegger, Josef
Highlights: Kinematic punching theory for SFRC slabs considering flexural and translational deformations. Application of Variable Engagement Model to estimate the fiber contribution to punching strength. Validation of the kinematic theory by means of systematic test series and a databank evaluations. Investigation of the influence of fiber properties on punching strength. Abstract: There are several possibilities to enhance the punching shear behavior of reinforced concrete slabs. Among them, various shear reinforcement systems have been found to efficiently increase both the punching strength and the deformation capacity compared to similar slabs without shear reinforcement. Nevertheless, the biggest disadvantage of shear-reinforced concrete slabs is the large effort associated with the installation of the reinforcement elements. Another efficient solution to improve the punching shear behavior of slab-column connections is the application of steel fibers in the region of the column. Depending on the fiber volume and fiber properties, steel fibers may significantly enhance the tension-softening behavior of concrete leading to higher punching strengths combined with a more ductile failure mode. In this paper, the existing two-parameter kinematic theory for punching shear in reinforced concrete slabs is extended considering the beneficial effects of steel fibers on punching shear capacity. The contribution to the punching strength provided by fibers is determined based on a theoretical model described in literature. The model allows for the description of the tension-softening behavior of reinforced composites containing randomly orientated discontinuous fibers as a function of the normal opening of the failure crack. The proposed theory is validated by means of systematic punching test series with varying fiber volume and databank evaluations. Further parametric studies were conducted to analyze the influence of fiber properties on punching strength more in detail.